2014
DOI: 10.1002/cmdc.201300557
|View full text |Cite
|
Sign up to set email alerts
|

Developing an Irreversible Inhibitor of Human DDAH‐1, an Enzyme Upregulated in Melanoma

Abstract: Inhibitors of the human enzyme dimethylarginine dimethylaminohydrolase-1 (DDAH-1) can raise endogenous levels of asymmetric dimethylarginine (ADMA) and lead to a subsequent inhibition of nitric oxide synthesis. Herein, N5-(1-imino-2-chloroethyl)-L-ornithine (Cl-NIO) is shown to be a potent time- and concentration-dependent inhibitor of purified human DDAH-1 (KI = 1.3 ± 0.6 μM; kinact = 0.34 ± 0.07 min−1), with > 500-fold selectivity against two arginine-handling enzymes in the same pathway. An activity probe i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 31 publications
0
37
0
Order By: Relevance
“…The research group demonstrated that DDAH1 is overexpressed in melanoma cell lines compared to normal human epidermal melanocytes and that cellular inhibition of DDAH1 by N 5 -(1imino-2-chloroethyl)-L-ornithine (Cl-NIO) resulted in reduced nitric oxide production in the A375 melanoma cell line. The reduction in NO synthesis was measured by quantifying 3nitrotyrosine levels and total nitrate and nitrite in the cell culture supernatant and it was independent of changes in DDAH1 or iNOS expression (183). Unfortunately, this study did not assess the effects of DDAH1 inhibition by Cl-NIO on specific tumor parameters, such as tumor cell viability and proliferation in vitro and/or in vivo growth of xenograft tumors derived from A375 cells, or assess the impact on angiogenesis.…”
Section: Pharmacological Inhibition Of Ddah1 Activity In Cancermentioning
confidence: 99%
See 3 more Smart Citations
“…The research group demonstrated that DDAH1 is overexpressed in melanoma cell lines compared to normal human epidermal melanocytes and that cellular inhibition of DDAH1 by N 5 -(1imino-2-chloroethyl)-L-ornithine (Cl-NIO) resulted in reduced nitric oxide production in the A375 melanoma cell line. The reduction in NO synthesis was measured by quantifying 3nitrotyrosine levels and total nitrate and nitrite in the cell culture supernatant and it was independent of changes in DDAH1 or iNOS expression (183). Unfortunately, this study did not assess the effects of DDAH1 inhibition by Cl-NIO on specific tumor parameters, such as tumor cell viability and proliferation in vitro and/or in vivo growth of xenograft tumors derived from A375 cells, or assess the impact on angiogenesis.…”
Section: Pharmacological Inhibition Of Ddah1 Activity In Cancermentioning
confidence: 99%
“…Studies to date have demonstrated an increase in DDAH1 protein expression in human glioma, meningioma, prostate cancer, and hepatocellular carcinoma, primarily by means of large-scale proteomic analysis. An upregulation of DDAH1 protein has also been observed in cohorts of melanoma and breast cancer cell lines, relative to normal melanocyte, and mammary epithelial cells, respectively (183,187). Aside from the identification that DDAH1 expression is significantly altered in these cancers, only a handful of these studies undertook further analysis into the specific role and function of DDAH1 within each cancer context.…”
Section: Expression Of Ddah Is Altered In Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…As such, several classes of DDAH inhibitors have been described in the literature. 32,34,35 Conversely, modifications of the carboxylic acid functional group have not been extensively investigated. 2).…”
Section: Introductionmentioning
confidence: 99%